Clinical predictors and explant lung pathology of acute exacerbation of idiopathic pulmonary fibrosis. Issue 4 (5th October 2020) - Dotan, Yaniv; Shapiro, William B.; Male, Eneida; Dominguez, Eduardo C.; Aneja, Amandeep; Huaqing, Zhao; Dass, Chandra; Shenoy, Kartik; Marchetti, Nathaniel; Cordova, Francis C.; Criner, Gerard J.; Mamary, A. James
Background: Idiopathic pulmonary fibrosis (IPF) is characterised by constant threat of acute exacerbation of IPF (AE-IPF). It would be significant to identify risk factors of AE-IPF. We sought to determine the prognostic value of lung transplantation candidacy testing for AE-IPF and describe explant pathology of recipients with and without AE-IPF before lung transplantation. Methods: Retrospective cohort study of 89 IPF patients listed for lung transplantation. Data included pulmonary function testing, echocardiography, right heart catheterisation, imaging, oesophageal pH/manometry and blood tests. Explanted tissue was evaluated by pulmonary pathologists and correlated to computed tomography (CT) findings. Results: Out of 89 patients with IPF, 52 were transplanted during stable IPF and 37 had AE-IPF before transplantation (n=28) or death (n=9). There were no substantial differences in candidacy testing with and without AE-IPF. AE-IPF had higher rate of decline of forced vital capacity (FVC) (21±22% versus 4.8±14%, p=0.00019). FVC decline of >15% had a hazard ratio of 7.2 for developing AE-IPF compared to FVC decline of <5% (p=0.004). AE-IPF had more secondary diverse histopathology (82% versus 29%, p<0.0001) beyond diffuse alveolar damage. There was no correlation between ground-glass opacities (GGO) on chest CT at any point to development of AE-IPF (p=0.077), but GGO during AE-IPF predicted secondary pathological process beyond diffuse alveolar damage. Conclusions: Lung transplantation candidacy testing including reflux studies did not predict AE-IPF besides FVC absolute decline. CT did not predict clinical or pathological AE-IPF. Secondary diverse lung pathology beyond diffuse alveolar damage was present in most AE-IPF, but not in stable IPF. Transplant candidacy testing fails to predict acute exacerbation of IPF besides FVC absolute decline. Patients transplanted during acute exacerbation of IPF reveal multiple secondary lung histopathological processes beyond the expected DAD. https://bit.ly/3e1CPjO